2012
DOI: 10.1021/op200233r
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scaleable Synthesis of a Geminal Dimethyl Tertiary Amine as an Inhaled Muscarinic Antagonist for the Treatment of COPD

Abstract: An efficient and scalable process for the synthesis of muscarinic antagonist, PF-3635659 1, is described, illustrating redesign of an analogue-targeted synthesis which contained a scale-limiting rhodium-activated C−H amination step. The final route includes a reproducible modified Bouveault reaction which has not previously been reported on a substrate of this complexity, or on such a scale with over 5 kg of the requisite gem-dimethylamine prepared via this methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Cumming et al reported multikilogram scale stereoselective synthesis of a novel anti-inflammatory agent ( 131 , PH46A), which has completed phase 1 clinical trial (BioMed Central ISRCTN Registry, 2014). Dillon et al developed a kilogram-scale synthesis of tetrasubstituted carbon-containing muscarinic antagonist 132 (PF-3635659) to support clinical studies . This compound has been investigated in phase 2 clinical trial in COPD patients (NCT01033487).…”
Section: Quaternary or Tetrasubstituted Carbon-containing Molecules T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cumming et al reported multikilogram scale stereoselective synthesis of a novel anti-inflammatory agent ( 131 , PH46A), which has completed phase 1 clinical trial (BioMed Central ISRCTN Registry, 2014). Dillon et al developed a kilogram-scale synthesis of tetrasubstituted carbon-containing muscarinic antagonist 132 (PF-3635659) to support clinical studies . This compound has been investigated in phase 2 clinical trial in COPD patients (NCT01033487).…”
Section: Quaternary or Tetrasubstituted Carbon-containing Molecules T...mentioning
confidence: 99%
“…Dillon et al developed a kilogram-scale synthesis of tetrasubstituted carbon-containing muscarinic antagonist 132 (PF-3635659) to support clinical studies. 155 This compound has been investigated in phase 2 clinical trial in COPD patients (NCT01033487). A multikilogram scale synthesis of BACE inhibitor (133, LY2886721) has been reported using a pilot scale flow synthesis.…”
Section: Carbon-containing Molecules That Entered Developmentmentioning
confidence: 99%
“…7,8 The intramolecular C(sp 3 )-H amination of sulfamates, interestingly, was applied to a scalable synthesis of a muscarinic antagonist but gram-scale reactions afforded the expected cyclic sulfamidate only in 50% yield. 9 More recent studies have concentrated on the search for efficient conditions for the intermolecular C(sp 3 )-H amination reaction, as its applicability has been long limited by a low efficiency and a narrow scope. High yielding and stereoselective reactions have been reported in the presence of sulfonimidamides as chiral nitrene sources, however, these processes remain of limited application since they involve chiral auxiliaries in stoichiometric amounts.…”
Section: Hn Cfmentioning
confidence: 99%
“…The latter allows for modification of specific sites according to the nature of the tethered nitrene source, with sulfamates being the most efficient and versatile nitrene precursors . The careful design of chiral rhodium­(II) complexes has led to the development of an asymmetric version for the synthesis of enantiopure substituted amines. , The intramolecular C­(sp 3 )–H amination of sulfamates, interestingly, was applied to a scalable synthesis of a muscarinic antagonist, but gram-scale reactions afforded the expected cyclic sulfamidate only in 50% yield …”
Section: Introductionmentioning
confidence: 99%